A Quantitative Study on Parental Influence and Lifestyle Factors in Child Obesity - Wang, Lujing; Li, Xueting (Pacific International Journal, 2024)
Child obesity is a growing global health concern, significantly impacting both developed and developing countries. This study examines the influence of parental behaviors and lifestyle factors on child obesity in Keyouqianqi, Inner Mongolia, China. Employing a quantitative research design, data was collected from 50 parents of obese children through structured questionnaires. Statistical analyses revealed significant associations between parental promotion of healthy eating, physical activity encouragement, and lower obesity rates, whereas restrictive feeding practices were linked to higher obesity rates. Lifestyle factors such as high-calorie food consumption, sugary beverage intake, insufficient physical activity, and excessive screen time were also significantly associated with child obesity. The findings underscore the importance of comprehensive interventions addressing both parental behaviors and children’s lifestyle choices to combat child obesity effectively.